THE USE OF WEB-BASED TASKS AND INTERNET SOURCES TO ENHANCE TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) - Svetlana Toropovienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2020)
Nowadays, English for Specific Purposes (ESP) becomes as important as other professional subjects taught such as Physics, Mechanics, Graphic Design, Material Science, etc. This paper aims at examining the application of web-based tasks and Internet resources for subject revision in English for Specific Purposes (ESP), motivating students for challenges in their real professional field and drawing conclusions about the application of the suitability of the above-mentioned tools for language learning. The presented ideas are supported by survey results and the observation of students’ behaviour during the lectures while applying web-based assignments. Moreover, the article provides a few examples of such activities used in ESP classes, seeks to enhance foreign language professional skills (listening, reading, writing, speaking) of a future modern specialist in an engineering field.